Pattern of Collection and Distribution of Zakat Fitrah 1444 H in ZISWAF Laboratory FEBI - Onti Laura Citra; Lanaa Fauziyyah; Pajar Wijaya; Andi Harpepen (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This journal is entitled "Pattern of Collection and Distribution of Zakat Fitrah 1444 H in the ZISWAF FEBI Laboratory. The background for writing this journal is due to the phenomenon of the lack of interest of students in paying zakat fitrah at the ZISWAF FEBI Lab. This study uses a qualitative approach and descriptive research type. The research subjects were FEBI, amil, and mustahiq students in the FEBI ZISWAF Lab who were directly involved and understood the object of this study. Data collection techniques are carried out by means of observation, interviews, and documentation. Based on the research results, it can be seen that the management and distribution of zakat fitrah in the ZISWAF FEBI Lab is in accordance with the Al-Qur'an, hadith and the opinion of the Shafi'I school of thought. This can be proven by the distribution of zakat fitrah evenly to all people, especially distribution to orphanages in the Betungan area, Berngkulu. And the distribution of zakat fitrah a few days after Eid al-Fitr. A value of worship that was obtained by the committee, the availability of the ZISWAF FEBI Lab as a place for managing zakat fitrah, and management and distribution time which is free time became an opportunity for the committee. While the obstacles related to the management and distribution of zakat fitrah in the ZISWAF FEBI Lab is the lack of interest of students, especially the Faculty of FEBI in paying zakat fitrah for the ZISWAF FEBI Lab.